Integrity of Financial Statements Reviewed from Corporate Governance, Leverage, and Company Size - Rahma, Khaza Akmalia; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of institutional ownership, managerial ownership, independent commissioners, audit committees, leverage, and company size on the integrity of financial statements in infrastructure companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The population in this study is infrastructure companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study uses a purposive sampling technique, obtained from 10 companies so that the number of samples used is 40 observation data. The analysis used in this study is multiple regression analysis using SPSS version 26 as a calculation tool. Based on the results in this study, it is shown that institutional ownership, managerial ownership, independent commissioners, and leverage have no effect on the integrity of financial statements. Meanwhile, the size of the company showed a negative effect on the integrity of the financial statements and the audit committee had a positive effect on the integrity of the financial statements.